Handed heirlooms narrative, photography, and postmemory in W.G. Sebald's The Rings of Saturn, Austerliz, and The Emigrants - Tolentino, Inah Beatriz R.; Villareal, Corazon D. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2016)
Throughout the course of Sebaldian studies there has been minimal contribution to how the framework of postmemory can be read into Sebald's texts. Moreover, most scholars address usage of photography in Sebald's works as merely indexical and deictic, which is one of the aspects that this study attempts to dispute. Postmemory, a concept recently proposed by Marianne Hirsch in her foundational book The Generation of Postmemory, is defined as the transmission of trauma from the first to the second-generation which is mediated by creative outputs such as narratives and photographs. Trauma is deeply embedded in navigating postmemories, and it is indeed trauma that drives the narratives and photographs of W.G. Sebald. Weaving these aspects together, this study argues that the construction of postmemory in three novels of Sebald studied here is dependent on specifically two modes of transmission-narratives of trauma and photographs of trauma. The novels which comprise this study's corpus are The Rings of Saturn, Austerlitz, and lastly, The Emigrants.
Thesis (B.A. in Comparative Literature)
Includes bibliographical references
Keywords: Memory in literature; Psychic trauma in literature